2021
DOI: 10.12998/wjcc.v9.i12.2778
|View full text |Cite
|
Sign up to set email alerts
|

Predictive risk factors for recollapse of cemented vertebrae after percutaneous vertebroplasty: A meta-analysis

Abstract: BACKGROUND As one of the most common complications of osteoporosis, osteoporotic vertebral compression fracture (OVCF) increases the risk of disability and mortality in elderly patients. Percutaneous vertebroplasty (PVP) is considered to be an effective, safe, and minimally invasive treatment for OVCFs. The recollapse of cemented vertebrae is one of the serious complications of PVP. However, the risk factors associated with recollapse after PVP remain controversial. AIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…According to previous histological and radiological studies, 4,5,16 it is mainly associated with osteonecrosis, nonunion, and pseudarthrosis after OVFs. Many researchers have demonstrated that the presentation of IVCs indicated instability within the injured vertebrae in different body postures 3,5–9 . Hence, the patients suffering from OVFs with IVCs usually have severe back pain and do not respond to conservative treatments such as bed rest and medication.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous histological and radiological studies, 4,5,16 it is mainly associated with osteonecrosis, nonunion, and pseudarthrosis after OVFs. Many researchers have demonstrated that the presentation of IVCs indicated instability within the injured vertebrae in different body postures 3,5–9 . Hence, the patients suffering from OVFs with IVCs usually have severe back pain and do not respond to conservative treatments such as bed rest and medication.…”
Section: Discussionmentioning
confidence: 99%
“…That may lead to unstable internal structure, which changes the ratio of PD and the anterior and posterior height of the vertebral body, and thus increases the risk of postoperative re-fracture. 19 …”
Section: Discussionmentioning
confidence: 99%
“…That may lead to unstable internal structure, which changes the ratio of PD and the anterior and posterior height of the vertebral body, and thus increases the risk of postoperative re-fracture. 19 Limitations: This is a retrospective design and shorter follow up study, and sample size is small. Therefore, there is a need for further larger studies, clinical trials and studies with longer follow-up times to evaluate the prognosis of patient.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 97%
“…Recently, several studies have analyzed the risk factors-decreased bone mineral density (BMD), cement leakage into the disc, sagittal imbalance, the presence of an intravertebral cleft, endplate cortical disruption, and the degree of restoration of the vertebral height-associated with SNVCFs after VP. [10][11][12][13][14][15] However, the results are contradictory and remain inconclusive. Furthermore, whether SNVCFs are caused by VP or by spontaneous progression of osteoporosis is yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%